2015
DOI: 10.3329/baj.v17i2.24658
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NPK and plant extracted pyroligneous acid on yield of Boro rice

Abstract: not availableBangladesh Agron. J. 2014, 17(2): 95-97

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Similarly, they been used as fertilizer in Aman rice production (Masum, et al, 2013) as well as tomatoes yield enhancers (Mungkunkamchao, et al, 2013). Thus the effectiveness of wood vinegar and tar use as soil amendment tools is dependant on their chemical compositions.…”
Section: Potential Applications Of Banana Wastes Vinegar and Tarmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, they been used as fertilizer in Aman rice production (Masum, et al, 2013) as well as tomatoes yield enhancers (Mungkunkamchao, et al, 2013). Thus the effectiveness of wood vinegar and tar use as soil amendment tools is dependant on their chemical compositions.…”
Section: Potential Applications Of Banana Wastes Vinegar and Tarmentioning
confidence: 99%
“…Similarly, they observed that spraying leaves of plants with wood vinegar helps strengthen the stems and makes the leaves greener and tolerant to pest and diseases thereby increasing crop yield. According to Mungkunkamchao et al (2013), Petter, et al (2013 and Masum, et al (2013) mixing wood vinegar with the commercial fertilizers proportionately have had positive effects on the overall yield of tomatoes, rice, wheat, maize, soybeans among other cereal crops thus making wood vinegar an excellent soil conditioner.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kang et al (2008) reported that mixing wood vinegar with carbon-based soil amendments combined with chemical fertilizers improved the yield and grain quality of rice compared to chemical treatments alone. Similarly, Masum et al (2013) showed that combination of wood vinegar and 50% RR of chemical fertilizer improved the yield of T. aman rice while wood vinegar applied to the soil surface increased the population of beneficial microbes and promote plant root growth (Tancho, 2008).…”
Section: Introductionmentioning
confidence: 99%